36 Views of Mount Fuji : On Finding Myself in Japan - Davidson, Cathy N., 1949- (Book collections on Project MUSE., 2006)
By turns candid, witty, and poignant, 36 Views of Mount Fuji is an American professor's much-praised memoir about her experiences of Japan and the Japanese.